ANALISIS IMPLEMENTASI NILAI-NILAI BUDAYA KERJA DI LINGKUNGAN BPSDMD MENUJU NTB CORPORATE UNIVERSITY - Syarif Lutfim (Jurnal Ilmiah Hospitality, 2022)
This research aims to determine the level of implementation, the application of Basic Values of Work Culture (NDBK) in the Regional Human Resources Development Agency (BPSDMD) of NTB Province, the second is to assist organizations in internalizing organizational culture at BPSDMD towards the implementation of NTB Corporate University (CorpU). The data collection technique in this research is by providing a set of written questions or statements submitted to 88 respondents to be answered by the person concerned. The questionnaire used in this research is the Questionnaire on the Implementation of Work Culture Development in Government Agencies based on the Regulation of the State Minister for Apparatus Empowerment. State Number PER/01/2007 concerning Guidelines for Evaluation of Implementation of Work Culture Development in Government Agencies. The results of the research are that the Application of Basic Work Culture Values in Work Behavior 17 pairs of Work Culture Values in the NTB Province BPSDMD Environment In general, it has been implemented well in BPSDMD, this is shown by the employees overall giving Good rating with an average score of 4.05. The application of the basic values of work culture in leadership and management at the NTB Province BPSDMD by employees overall gave a GOOD rating with an average score of 4.1. Employees overall gave a GOOD rating with an average score of 4.04.